The Routledge companion to English folk performance
1 online resource
Keywords: This broad-based collection of essays is an introduction both to the concerns of contemporary folklore scholarship and to the variety of forms that folk performance has taken throughout English history. Combining case studies of specific folk practices with discussion of the various different lenses through which they have been viewed since becoming the subject of concerted study in Victorian times, this book builds on the latest work in an ever-growing body of contemporary folklore scholarship. Many of the contributing scholars are also practicing performers and bring experience and understanding of performance to their analyses and critiques. Chapters range across the spectrum of folk song, music, drama and dance, but maintain a focus on the key defining characteristics of folk performance - custom and tradition - in a full range of performances, from carol singing and sword dancing to playground rhymes and mummers' plays. As well as being an essential reference for folklorists and scholars of traditional performance and local history, this is a valuable resource for readers in all disciplines of dance, drama, song and music whose work coincides with English folk traditions.